Navigating complex choices through legitimation: Narrative strategies in risk-reduction mastectomy decision-making among unaffected women with genetic risk for breast cancer in Switzerland - Maria Caiata-Zufferey; Reka Schweighoffer; Monica Aceti; Carla Pedrazzani; Maria C. Katapodi; Souria Aissaoui; Mekdes Alemu; Murat Aykut; Fulvia Brugnoletti; Rachel Bunger; Nicole Bürki; Pierre O. Chappuis; et al. (SSM: Qualitative Research in Health)
For unaffected women at high risk for developing breast cancer due to pathogenic variants in BRCA1 or BRCA2 (BRCA) genes, bilateral risk-reducing mastectomy (RRM) is an alternative to intensive surveillance. RRM reduces breast cancer risk but may generate additional health and psychosocial issues, making the choice between surveillance and RRM complex and personal. This grounded theory study explores how unaffected women carrying BRCA pathogenic variants engage in a decision-making process leading to the choice of undergoing RRM. Narrative data were collected in Switzerland through biographical interviews with 38 unaffected women carrying BRCA pathogenic variants. Participants had either undergone RRM or were planning the surgery in the future. Findings indicate that the decision to undergo RRM was influenced by femininity and body image, current life engagements, anticipation of surgery risks and outcomes, perception and acceptance of cancer risk, surveillance experiences, attitudes of healthcare providers and family, and financial considerations. These factors interacted, creating contradictions that made decision-making challenging. To navigate this uncertainty, women progressively built their decision through a triple process of making sense: framing RRM as an obligated, empowering and mundane choice. This sense-making process is described as a process of legitimation, through which women decide to undergo RRM and integrate it into their life trajectory, ensuring its acceptability for themselves and their social circles. The discussion provides insights into the legitimation process as a heuristic tool for exploring crucial choices in uncertainty and offers implications for healthcare providers assisting individuals in complex decision-making processes.